The Role of Financial Literacy and Overconfidence in Investment Decision Making (Case Study on Master of Management Students of Diponegoro University, Semarang) - Thesman, Meilin; Wahyudi, Sugeng (The Islamic Education and Multiculturalism Foundation, 2024)
The right investment decision is based on how well financial literacy is owned and controlling financial behavior, namely overconfidence. In general, the higher the level of education, the better. The purpose of this study was to analyze the Role of Financial Literacy and Overconfidence in Investment Decision Making at the Education level of Master of Management Students at Diponegoro University Semarang. With a sample of 127 respondents, from batches 58-63 in 2024. The data analysis method uses the measurement model (Outer Model) and the Struktrual Model (Inner Model) in testing the model researchers apply Structural Equation Modeling-Partial, Least Square (SEM-PLS). The results showed the first hypothesis, namely financial literacy has a significant positive effect on investment decisions, the second hypothesis, namely overconfidence has a significant positive effect on investment decisions and overconfidence can moderate (strengthen) the relationship between financial literacy and investment decisions in Master of Management Students at Diponegoro University Semarang in 2024.